Strategi Adaptasi Nelayan Dan Perkembangan Modernisasi Perikanan Di Kota Baubau - La Ode Abdul Munafi; Andi Tenri (DIMENSI - Journal of Sociology, 2016)
This study aims to decipher the patterns of adaptation strategies fishers in Baubau city in response to the demands of the modernization of the fisheries began to explore the area since the end of the decade of 1970 an.Penelitian using the data kualitatif.Pengumpulan done through interviews, observation, and conducted dokumentasi.Penelitian the fishing communities in the City Bone-Bone Baubau.Analisis data were analyzed descriptively-kualitatif.Hasil research showsthat in responding to the demands of the development of the modernization of the fisheries, the fishermen in the City Baubau generally selecting adaptation strategies. This strategy is the fishermen through motorisation boat (fleet) catch in the various types and sizes, the adoption of modern fishing gear innovation, and establish a working relationship (partnership) with modern fisheries entrepreneurs. Selection of adaptation strategies through three approaches, functionally deliver fishermen can increase productivity results, although on the other hand appears the impact thatputs them in a position exploited in the construction of a working relationship with a modern fisheries entrepreneurs.